2015
DOI: 10.1103/physreva.92.043831
|View full text |Cite
|
Sign up to set email alerts
|

Precision estimation of source dimensions from higher-order intensity correlations

Abstract: An important topic of interest in imaging is the construction of protocols that are not diffraction limited. This can be achieved in a variety of ways, including classical superresolution techniques or quantum entanglement-based protocols. Here, we consider superresolving imaging in the far field using higher-order intensity correlations. We show that third and fourth order correlations can improve upon the first and second order correlations that are traditionally used in classical optics and Hanbury Brown an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…We choose to work in the near-field regime over the far field. These define different regions of the electromagnetic field around the sources and allow the use of intensity measurements in the near field to estimate d as opposed to higher-order correlation measurements in the far field [21,22]. For complete state detection, the QFI remains invariant of the regime considered.…”
Section: Classical and Quantum Light Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose to work in the near-field regime over the far field. These define different regions of the electromagnetic field around the sources and allow the use of intensity measurements in the near field to estimate d as opposed to higher-order correlation measurements in the far field [21,22]. For complete state detection, the QFI remains invariant of the regime considered.…”
Section: Classical and Quantum Light Sourcesmentioning
confidence: 99%
“…It is well known that quantum resources provide improvements to the estimation sensitivities of * jsidhu1@sheffield.ac.uk † p.kok@sheffield.ac.uk physical parameters, and this has been demonstrated for phase estimations in interferometers [15][16][17][18]. Such resources are exploited in quantum imaging to drive resolution capabilities past the Abbe-Rayleigh criterion [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The Hanbury Brown and Twiss (HBT) effect [1,2] discovered in 1956 was at the heart of the development of the field of quantum optics. Indeed, this discovery led to numerous remarkable multiphoton experiments which have not only deepened our fundamental understanding of multiphoton interference [3][4][5][6][7][8][9] but have also led to numerous applications in information processing [10][11][12][13][14][15] and imaging [16][17][18][19][20][21][22].…”
Section: Motivationmentioning
confidence: 99%
“…Here, we generalize the scheme to reconstruct any number of independent thermal light sources at arbitrary separations in one dimension exploiting intensity correlation functions of order m ≥ 3. We present experimental results confirming the imaging protocol and provide a rigorous mathematical proof for the obtained subclassical resolution.Higher order interferences with photons emitted by statistically independent light sources are an active field of research with the potential to increase the resolution in spectroscopy, lithography and interferometry [1][2][3][4][5][6], as well as in imaging and microscopy [7][8][9][10][11][12][13][14][15][16][17]. So far, subclassical resolution has been achieved by using entangled photons [3,8], but it was also shown that initially uncorrelated light fields -non-classical as well as classical -can be employed for that purpose [13][14][15][16][17].…”
mentioning
confidence: 99%
“…So far, subclassical resolution has been achieved by using entangled photons [3,8], but it was also shown that initially uncorrelated light fields -non-classical as well as classical -can be employed for that purpose [13][14][15][16][17]. Recently, Oppel et al presented a detection scheme that allows to determine the source distance d for an array of N equidistant thermal light sources (TLS) with subclassical resolution by measuring the N th-order spatial intensity correlation function [14].…”
mentioning
confidence: 99%